Diet-induced obesity impairs spermatogenesis: a potential role for autophagy - Mu, Yang (Sci Rep, 2017)
Autophagy is an evolutionarily conserved process that plays a crucial role in maintaining a series of cellular functions. It has been found that autophagy is closely involved in the physiological process of spermatogenesis and the regulation of sperm survival and motility. However, the role of autophagy in high-fat diet (HFD)-induced impaired spermatogenesis remains unknown. This study was designed to investigate the role of autophagy in HFD-induced spermatogenesis deficiency and employed chloroquine (CQ) to inhibit autophagy and rapamycin (RAP) to induce autophagy. 3-methyladenine (3-MA) and CQ were administered via intratesticular injection in vivo. The effects of CQ and 3-MA on the parameters of spermatozoa co-cultured with palmitic acid (PA) in vitro were also investigated. Human semen samples from obese, subfertile male patients were also collected to examine the level of autophagy. The results suggested that HFD mice subjected to CQ showed improved spermatogenesis. Inhibiting autophagy with CQ improved the decreased fertility of HFD male mice. Moreover, the in vivo and in vitro results indicated that both CQ and 3-MA could suppress the pathological changes in spermatozoa caused by HFD or PA treatment. Additionally, the excessive activation of autophagy was also observed in sperm samples from obese, subfertile male patients.